Usoda maja '68 in (post)socializem - Juvan, Marko (Primerjalna književnost, 2020)
Based on the idea that "the imaginative proximity of social revolution" (Anderson) is decisive for modernism, the article discusses the neo-avant-garde radicalization of modernism in the 1960s and 1970s from the perspective of world-systems theory. The author focuses on the literary and theoretical field of capitalist France in comparison with the accelerated development of both fields in the socialist periphery of global modernism - in non-aligned Yugoslavia and its system of socialist self-management. The article interprets the connection between experimental literature and (post-)structuralist theory in Slovenia during "the long 1968". It developed from the original neo-avant-garde alliance to the split in the mid-1970s. Finally, the author presents different interpretations of the historical process between the attempted student revolution of 1968 and 1989, when globalized capitalism seized power over socialism and postmodernism entered modernism.
Keywords: književnost in družba; modernizem; neoavantgarda; revolucija; slovenska književnost; socializem; svetovni sistem; študentsko gibanje